Proceedings of the 3rd International Symposium on Big Data and Cloud Computing Challenges (ISBCC - 16') - Vijayakumar, V.; Neelanarayanan, V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This proceedings volume contains selected papers that were presented in the 3rd International Symposium on Big data and Cloud Computing Challenges, 2016 held at VIT University, India on March 10 and 11. New research issues, challenges and opportunities shaping the future agenda in the field of Big Data and Cloud Computing are identified and presented throughout the book, which is intended for researchers, scholars, students, software developers and practitioners working at the forefront in their field. This book acts as a platform for exchanging ideas, setting questions for discussion, and sharing the experience in Big Data and Cloud Computing domain.
Computer Security: Information security, Network Security, Cloud Security, Mobile Security -- Wireless Sensor Network -- Cloud Computing -- Image Processing -- Big Data -- Internet of Things -- Artificial Intelligence -- Software Engineering.
Keywords: Computational intelligence; Artificial intelligence; Data structures (Computer science).; Information theory; Data mining; Application software; Computational Intelligence; Artificial Intelligence; Data Structures and Information Theory; Data Mining and Knowledge Discovery; Computer and Information Systems Applications